2022
DOI: 10.1016/j.envpol.2021.118678
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the functioning and structure of the PE and PP plastispheres from the Mediterranean Sea

Abstract: Plastic debris are accumulating in the marine environment and aggregate microorganisms that form a new ecosystem called the plastisphere. Better understanding the plastisphere is crucial as it has self-sufficient organization and carries pathogens or organisms that may be involved in the pollutant adsorption and/or plastic degradation. To date, the plastisphere is mainly described at the taxonomic level and the functioning of its microbial communities still remains poorly documented. In this work, metagenomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 39 publications
1
41
4
Order By: Relevance
“…While previous studies reported diatoms (Mincer et al, 2016), Arthropoda (Delacuvellerie et al, 2021), fungi (Kettner et al, 2017), and ascidians (Vieira et al, 2018) as pioneer colonizers of artificial surfaces in the marine environment, our results show that Cnidaria, and particularly the invasive hydroid of the Bougainvillia genus, was the main taxon detected in the eukaryotic dataset during the early stages of recruitment (week-1 and -3). Bougainvillia's explosive growth could have been favored by the chemical cues from the bio-polymers (Wyatt et al, 2005;Grey et al, 2018) and/or the lack of competition during the early stage of colonization (Rinkevich and Sakai, 2001;Lindquist, 2002).…”
Section: Recruitment Patterns Of Non-indigenous Species On Bio-polymerscontrasting
confidence: 87%
“…While previous studies reported diatoms (Mincer et al, 2016), Arthropoda (Delacuvellerie et al, 2021), fungi (Kettner et al, 2017), and ascidians (Vieira et al, 2018) as pioneer colonizers of artificial surfaces in the marine environment, our results show that Cnidaria, and particularly the invasive hydroid of the Bougainvillia genus, was the main taxon detected in the eukaryotic dataset during the early stages of recruitment (week-1 and -3). Bougainvillia's explosive growth could have been favored by the chemical cues from the bio-polymers (Wyatt et al, 2005;Grey et al, 2018) and/or the lack of competition during the early stage of colonization (Rinkevich and Sakai, 2001;Lindquist, 2002).…”
Section: Recruitment Patterns Of Non-indigenous Species On Bio-polymerscontrasting
confidence: 87%
“…is frequently associated to marine algae [ 53 ]. These associations support the fact that the plastisphere may be a self-sufficient ecosystem [ 54 ], with many ecological relations among its members that include symbionts, saprotrophs and parasites [ 55 ]. The communities we have identified living on MFs in the Mediterranean Sea form distinct groups in relation to the sampling seasons (summer and spring) ( Fig 4 ).…”
Section: Resultsmentioning
confidence: 70%
“…To date, only a few studies have reported bacteria that could be a putative human pathogen on MFs or other types of microplastics in Mediterranean waters [ 49 , 54 ]. This study is the first to describe V. parahaemolyticus on floating MFs at the region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adverse health effects associated with the intake of MPs by marine species include physical damage, tissue abrasion and mechanical obstruction (Pozo et al, 2019). The release of plastic additives J o u r n a l P r e -p r o o f Journal Pre-proof and adsorbed toxic elements, persistent organics and substances of concern such as antibiotics and even microorganisms may occur during digestion of MPs in the digestive tracts of marine species (Caruso, 2019;Yu et al, 2021) (Delacuvellerie et al, 2022). Thus, MPs can be vectors of toxic chemicals and their intake could result in toxicity to aquatic life (Pannetier et al, 2020).…”
Section: Introductionmentioning
confidence: 99%